1993
DOI: 10.1139/z93-022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mandibular with cemental growth-layer counts for ageing Atlantic walrus (Odobenus rosmarus rosmarus)

Abstract: The relationship between the numbers of growth layers counted in the mandible and in the cementum of lower canines from 87 walrus (Odobenus rosmarus rosmarus) was examined. A 1:1 correlation between counts of growth layers in the two tissues was found in males ≤ 19 years old and females ≤ 9 years old. No correlation was found in males with ≥ 21 or in females with ≥ 10 cemental growth layers. In physically mature walrus, mandibular layering was unreliable for age analysis. Resorption and a reduced mandibular gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…Capture dates ranged from 1988 to 1996. Mandibular teeth were extracted at time of capture (or, in the case of Greenland samples, from mandibles in the laboratory) for later sectioning and ageing by enumeration of dental cementum growth layers (Garlich-Miller et al, 1993). Teeth were chosen as indicator tissues for isotope analysis because they grow incrementally through life and are not resorbed (Fay, 1982;Hillson, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…Capture dates ranged from 1988 to 1996. Mandibular teeth were extracted at time of capture (or, in the case of Greenland samples, from mandibles in the laboratory) for later sectioning and ageing by enumeration of dental cementum growth layers (Garlich-Miller et al, 1993). Teeth were chosen as indicator tissues for isotope analysis because they grow incrementally through life and are not resorbed (Fay, 1982;Hillson, 1986).…”
Section: Methodsmentioning
confidence: 99%
“…Females Ͻ 5-yr-old and males Ͻ 7-yr-old were considered juveniles (MacLaren, 1958). Ages of walrus were determined by counting dental annuli in the teeth (Garlich-Miller et al, 1993). Females Ͻ 6-yrold and males Ͻ 8-yr-old were considered to be juveniles (Fay, 1985).…”
Section: Pinnipedsmentioning
confidence: 99%
“…Generally, cementum in delphinids and phocoenids is not well developed and has inconspicuous layers so dentine is used for age estimation (Lockyer et al 1981, Myrick et al 1983, Hohn 2009). Cementum normally provides better clarity of GLGs for carnivores such as pinnipeds, sea otters and polar bears because the pulp cavity often becomes occluded (e.g., McLaren 1958a,b, Hewer 1964, Dietz et al 1991, Garlich-Miller et al 1993, Stewart et al 1996, Calvert and Ramsay 1998, Amano et al 2000 or dentine deposition is too irregular to resolve GLGs, especially last-deposited small layers (Myrick et al 1983, Bjørge et al 1995, Hohn 2009). …”
Section: Nammco Scientific Publications Volume 10 11mentioning
confidence: 99%
“…Thus, most studies have found significantly fewer GLGs than in other hard tissues, e.g., teeth, in the same animal, especially in older animals (Nishiwaki et al l961, Kleinenberg and Klevezal 1962, Petersen and Born 1982, Garlich-Miller et al 1993. Therefore, the use of most bones to obtain absolute age estimates is unsatisfactory when age can be obtained using other tissue or methods.…”
Section: Other Bonesmentioning
confidence: 99%